2020
DOI: 10.1158/1541-7786.mcr-19-0561
|View full text |Cite
|
Sign up to set email alerts
|

UBE2C Is Upregulated by Estrogen and Promotes Epithelial–Mesenchymal Transition via p53 in Endometrial Cancer

Abstract: Ubiquitin-conjugating enzyme E2C (UBE2C) plays important roles in tumor progression; nevertheless, its function in endometrial cancer remains unclear. This study elucidated the impact of UBE2C on endometrial cancer and its underlying mechanism. Human endometrial cancer and normal endometrial tissues were acquired from patients at Wuhan Union Hospital and UBE2C expression was detected by Western blotting and qRT-PCR. Endometrial cancer cells were transfected with a UBE2C overexpression plasmid or UBE2C-specific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 47 publications
3
76
0
Order By: Relevance
“…Moreover, UBE2C induces Wnt/β-catenin and PI3K/Akt signaling to regulate phosphorylation levels of Aurora-A for epithelial-mesenchymal transition (EMT) in gastric adenocarcinoma [38]. UBE2C promotes EMT via p53 and p21 in endometrial cancer [39]. Our results indicated that UBE2C was involved in cell invasion and migration in OSCC cells ( Figure 3); higher UBE2C expression was associated with lymph node metastasis in OSCC patients ( Supplementary Table S1) and with poor DSS in TSCC patients having lymph node metastasis (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, UBE2C induces Wnt/β-catenin and PI3K/Akt signaling to regulate phosphorylation levels of Aurora-A for epithelial-mesenchymal transition (EMT) in gastric adenocarcinoma [38]. UBE2C promotes EMT via p53 and p21 in endometrial cancer [39]. Our results indicated that UBE2C was involved in cell invasion and migration in OSCC cells ( Figure 3); higher UBE2C expression was associated with lymph node metastasis in OSCC patients ( Supplementary Table S1) and with poor DSS in TSCC patients having lymph node metastasis (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Except for physiological structure variation on male and female, the gender-based immunity diversity is showed to account for the difference of sexual hormone secretion, such as estrogen, progestogen and androgen. However, the function of estrogen in cancer research still emphasized on the cancer cell proliferation [ 2 ], angiogenesis [ 3 ], epithelial–mesenchymal transition (EMT) [ 4 ], while the estrogen-induced cancer immune response alternation remains unclear. This review emphasized on the cell modification induced by estrogen and its receptor, estrogen receptor (ER), in canonical and non-canonical manner.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that Ube2c may have a multi-directional promotion effect on hepatocyte proliferation. Studies on the mechanism of UBE2C expression indicate that the expression of UBE2C may be stimulated by androgen- or estrogen-receptor, lncRNA and miRNA ( Kato et al, 2016 ; Gu et al, 2017 ; Hu et al, 2019 ; Liu et al, 2020 ). These provide a general direction for us to further study the reasons for the up-regulation of Ube2c in the early stage of liver regeneration.…”
Section: Discussionmentioning
confidence: 99%